2018
DOI: 10.5334/ijic.3078
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-experimental Study of Systematic Screening for Family Planning Services among Postpartum Women Attending Village Health and Nutrition Days in Jharkhand, India

Abstract: Background:Systematic screening helps increase family planning uptake through integration with other services, including immunization. Though successfully demonstrated at health facilities, this strategy has not been demonstrated in communities. This study assessed the effectiveness of systematic screening to increase postpartum family planning use during community health days in India without adversely affecting immunization services.Methods:The study was conducted during 180 individual Village Health and Nut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…The finding of this review was similar to the cohort study conducted in Zimbabwe and Nigeria. 37,38 Nevertheless, the pooled effect size of the study conducted by Balasubramaniam et al, 39 Azmat et al, 31 and Charles-eromosele and Odeyemi 40 were 1.1%, 7.4%, and 1.8%, respectively. These researchers used only routine counseling and face-to-face lecture health education delivery methods.…”
Section: Discussionmentioning
confidence: 89%
“…The finding of this review was similar to the cohort study conducted in Zimbabwe and Nigeria. 37,38 Nevertheless, the pooled effect size of the study conducted by Balasubramaniam et al, 39 Azmat et al, 31 and Charles-eromosele and Odeyemi 40 were 1.1%, 7.4%, and 1.8%, respectively. These researchers used only routine counseling and face-to-face lecture health education delivery methods.…”
Section: Discussionmentioning
confidence: 89%
“…Offering the option of multiple opportunities to engage with family planning providers could remove perceived barriers to contraception use in the postpartum period. Prior research demonstrated that screening for interest in family planning services at village health and nutrition days where vaccinations occur in India was associated with an increase in women later seeking family planning services through the public health system [ 15 ]. We propose a strategy to utilize the infant vaccination visit as an opportunity to reach postpartum women in the community to provide family planning care, including all reversible contraceptive methods through integrated maternal-infant health care visits [Theme 2: Linking contraceptive care and infant vaccination is perceived as potentially feasible and acceptable to implement by families, health workers, and community members].…”
Section: Discussionmentioning
confidence: 99%
“…Integration of postpartum family planning into infant vaccination services has been recommended as a strategy to improve family planning uptake worldwide by leveraging existing public health infrastructure. However, the effectiveness of this approach has not be consistently demonstrated [15][16][17][18]. In India, immunization services are one of the most widely implemented and successful public health programs [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An intrauterine device (IUD) is the most widely used method of contraception with approximately14.3 % of female contraceptive users prefer the IUD, globally [4,5]. 2 It is coitus-independent, reversible and effective form of contraception with immediate contraceptive action and have advantages: ease of insertion, minimal adverse impacts on breast feeding and cost effectiveness [6,7].…”
Section: Introductionmentioning
confidence: 99%